Static analysis and process model transformation for an advanced business process to Petri net mapping. (8th September 2017) - Heinze, Thomas S.; Amme, Wolfram; Moser, Simon
Summary: Verification of business processes typically relies on Petri net–based process models. While they allow for natural modeling and analysis of aspects such as parallelism and message exchange, such a process model is seldom complete and precise. This is mainly because the available techniques for deriving a Petri net model from the original model neglect process data in favor of feasible verification. In this paper, we present an approach for deriving more precise process models by leveraging a process‐to‐Petri‐net compiler, which takes as input a business process and generates as output a Petri net model for the process. This can be subsequently used for verification. However, in contrast to a conventional compiler, our compiler's objective is not to create the most efficient code but rather to produce a most precise but still effectively verifiable Petri net–based process model.